Impact of Factors Determining Retailing Culture in India and its Impact on the Online Shopping of Electronic Goods and in India: An Empirical Study - Ms. Prativindhya, Dr. Rajiv Kaushik (International Journal of Advanced Science and Technology, 2019)
Purpose of the Study: The study aims to find out that the factors determining the online shopping of electronic goods in India, which is an emerging market. The study related through empirical evidences the various salient features of online retailing to their intention to purchase the consumer electronic goods. Scope: The study is limited to the online retailing determinants in relation to the electronic goods industry. The geographic scope of the study is Delhi-NCR. The study comprehensively covers the various aspects of online retailing as independent variables consumer buying behavior towards electronic goods as dependent variables. Research Design & Methodology: The study is descriptive in nature. The data have been collected from the respondents who had made at least one online purchase of an electronic item in the last six months. The sample size of the study was 500 and the data has been analyzed with the help of regression analysis. Findings: The study finds that various determinants of online retailing have a positive and significant impact on online consumer buying behavior towards electronic products. Originality: The study determines the online retailing factorswith the items that have been newly explored in the present work only. The study has determined the association between the factors that support electronic buying Type: Empirical Research Paper Keywords: Retailing, Consumer Buying Behavior, Electronic Goods, Regression Analysis